2018
DOI: 10.1007/s10549-018-4779-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of dual mTOR inhibitor MLN0128 against everolimus-resistant breast cancer

Abstract: Among the many signaling transduction pathways, which are altered post everolimus resistance, targeting dual mTORC1/2 is a possible option for patients who have recurrent disease from previous everolimus treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…So far, another dual mTOR inhibitor, MLN0128 is used only in vitro on cell models against everolimus-resistant breast cancer, and it inhibits the AKT phosphorylation. MLN0128 may suppress the proliferation of this kind of cell [ 195 ]. Bostner J and co-workers detected that raptor protein expression in the nucleus was increased in ER/PgR-positive and HER2-negative tumors with low grade, further associated with the luminal A subtype.…”
Section: Mtor Inhibitors: Everolimus and Temsirolimusmentioning
confidence: 99%
“…So far, another dual mTOR inhibitor, MLN0128 is used only in vitro on cell models against everolimus-resistant breast cancer, and it inhibits the AKT phosphorylation. MLN0128 may suppress the proliferation of this kind of cell [ 195 ]. Bostner J and co-workers detected that raptor protein expression in the nucleus was increased in ER/PgR-positive and HER2-negative tumors with low grade, further associated with the luminal A subtype.…”
Section: Mtor Inhibitors: Everolimus and Temsirolimusmentioning
confidence: 99%
“…AZD-2014, a dual mTORC1/2 inhibitor, showed superior activity than everolimus in vitro and in vivo in renal cell carcinoma [79] but demonstrate inferior efficacy in patients with renal cell carcinoma [80]. Therefore, although preliminary studies showed promising efficacy of dual mTOR inhibitors in various of cancers [81,82], the clinical significance should still be investigated in clinical trials to prove their activities in cancer treatment [83].…”
Section: Mtor Inhibitorsmentioning
confidence: 99%
“…Acquiring the resistance to mTOR inhibitors (most commonly rapamycin and its derivates) was detected in various tumours' models in vitro as well as in vivo in patients suffering from such conditions as i.a. breast cancers, gliomas 3 , 4 , 31 . The toxicity of mTOR inhibitors is widely known, the most commonly hematologic, gastrointestinal and metabolic side effects are observed.…”
Section: Discussionmentioning
confidence: 99%
“…TORC1 regulates mostly protein synthesis by phosphorylation of translation factors, TORC2 controls cell survival and cytoskeleton functions, both complexes are linked by AKT 3 .…”
Section: Introductionmentioning
confidence: 99%